Self expanding stents in congenital heart disease. Issue 4 (October 1994) - Redington, A N; Weil, J; Somerville, J
Abstract : OBJECTIVES–To show potential indications for and clinical use of self expanding stents in patients with congenital heart disease. DESIGN–Descriptive study of selected, non-randomised patients with balloon expandable but persistent stenoses in whom the use of a balloon expandable stent was considered suboptimal or impossible. SETTING–A tertiary referral centre. PATIENTS–10 patients, aged 15 days to 32 years. Six patients after atriopulmonary or cavopulmonary anastomosis, two with pulmonary atresia and multiple aortopulmonary collaterals, one with coarctation of the aorta, and one with congenital pulmonary venous stenosis. RESULTS–Successful, uncomplicated, placement of 10 stents with the desired haemodynamic results, even in tortuous vessels with many stenoses. CONCLUSIONS–Self expanding stents have a role in the treatment of patients with congenital heart disease. They should be considered when a smaller delivery system and flexibility would aid placement, or in the treatment of long or multiple sequential stenoses.